2017
DOI: 10.3390/ma10070782
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Stone Columns

Abstract: This paper reviews the main modeling techniques for stone columns, both ordinary stone columns and geosynthetic-encased stone columns. The paper tries to encompass the more recent advances and recommendations in the topic. Regarding the geometrical model, the main options are the “unit cell”, longitudinal gravel trenches in plane strain conditions, cylindrical rings of gravel in axial symmetry conditions, equivalent homogeneous soil with improved properties and three-dimensional models, either a full three-dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 85 publications
0
13
0
1
Order By: Relevance
“…An equivalent footing was considered at a depth of two-thirds the column and assuming a 2:1 load spread beneath the footing it was found that the induced stress at the tank boundaries were negligible (12%). Similar approach was presented by Ali et al [10] and Castro [46]. In the finite element model, test tank dimensions used in the experiments were considered for comparison of predicted results with experimental data.…”
Section: Finite Element Analysismentioning
confidence: 99%
“…An equivalent footing was considered at a depth of two-thirds the column and assuming a 2:1 load spread beneath the footing it was found that the induced stress at the tank boundaries were negligible (12%). Similar approach was presented by Ali et al [10] and Castro [46]. In the finite element model, test tank dimensions used in the experiments were considered for comparison of predicted results with experimental data.…”
Section: Finite Element Analysismentioning
confidence: 99%
“…The second type is for physical piles, which are currently made up of stone or colloidal silica grout without a chemical reaction with neighboring soil (Gallagher et al, 2007;Saoudi et al, 2013). The reinforced effect of the stone pile comes from its own mechanical properties Saoudi et al (2013), Castro (2017), while stabilization from colloidal silica can also be attributed to silica nanoparticle migration (Gallagher et al, 2007). On the whole, chemical piles are still more generally practiced in soil improvement, but the interest in physical piles such as silica nanoparticle has increased due to its eco-friendly characteristics and effectively stabilized effects.…”
Section: Introductionmentioning
confidence: 99%
“…Bu dört metot 2D olarak değerlendirilirken beşinci modelleme tekniği olarak vurgulanan "Full 3D" modelde ise sistem kompleks halde değerlendirilerek üç boyutlu analizler yapılmıştır [9]. Bu araştırmalar sonucunda, geleneksel taş kolon uygulamalarında analizlerin modellemeye uyumu açısından Castro 2017 yılında, birim hücre metodunun oturma ve konsolidasyonun analizinde uygun olup stabilite problemlerinde uygun olmadığını; düzlem gerilme modelinin ve homojenleştirme metodunun kullanıldığı çalışmalarda oturma, konsolidasyon ve stabilite problemlerinde kısmen uygun olduğunu ve 3D modelin kullanıldığı araştırmalarda oturma, konsolidasyon ve stabilite problemleri açısından tamamen uygun olduğunu ortaya koymuştur [10].…”
Section: Introductionunclassified